2022
DOI: 10.1371/journal.pone.0269537
|View full text |Cite
|
Sign up to set email alerts
|

Every day mitral valve reconstruction: What has changed over the last 15 years?

Abstract: Objective Mitral valve reconstruction (MVR) is one of the cardiosurgical procedures which cannot be substituted by any intervention owing to the quality of the quasi-anatomical, physiological repair. However, technique and strategies have changed over the years. We looked at procedural characteristics and outcome in an all-comer, non-selected cohort of patients. Methods 738 out of 1.977 patients were retrospectively analyzed receiving MVR with and without concomitant procedures. The cohort was divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a previous study, we looked at all aspects of mitral valve repair, such as ring annuloplasties (N = 738), Wooler plastic (N = 36), NeoChord implantation (N = 168), resections on AML and PML (N = 125), patch plastic on AML and PML (N = 10), plications on both, AML and PML (N = 124) and cleft closures between 2004 and 2019. This study analyzed the evolution of mitral valve reconstruction procedures over time [ 7 ]. For the purpose of a proper comparison of quadrangular resection with inverse plication, the present study compares the outcome of “inverse plication of PML” with quadrangular resection of the PML only.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we looked at all aspects of mitral valve repair, such as ring annuloplasties (N = 738), Wooler plastic (N = 36), NeoChord implantation (N = 168), resections on AML and PML (N = 125), patch plastic on AML and PML (N = 10), plications on both, AML and PML (N = 124) and cleft closures between 2004 and 2019. This study analyzed the evolution of mitral valve reconstruction procedures over time [ 7 ]. For the purpose of a proper comparison of quadrangular resection with inverse plication, the present study compares the outcome of “inverse plication of PML” with quadrangular resection of the PML only.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical mitral valve repair is the gold standard therapy for treating primary MR [ 1 , 3 , 4 , 5 , 6 , 7 ]. Refinement in techniques, in conjunction with standard annuloplasty, have led to excellent outcomes [ 8 ]. Long-term results are often reported as freedom from reoperation, which may lead to an underestimation of recurrent MR as surgery may be deferred in selected patients [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Refinement in techniques, in conjunction with standard annuloplasty, have led to excellent outcomes [ 8 ]. Long-term results are often reported as freedom from reoperation, which may lead to an underestimation of recurrent MR as surgery may be deferred in selected patients [ 8 , 9 , 10 ]. Few studies and centers have reported long-term outcomes following the repair of degenerative MR. Longitudinal assessment requires a dedicated infrastructure and intentional data collection.…”
Section: Introductionmentioning
confidence: 99%